Vespa Trash Culture Fan Communities in Bangkalan Madura - Teguh Hidayatul Rachmad (Communication Sphere, 2015)
Madura traditional Islamic culture started there since the Dutch colonial era in Indonesia,especially on the island of Madura. As the times , traditional culture has been fused with thecommunity Madura Madura , especially in Bangkalan. In today's era of modernity , traditionalculture has experienced a shift in meaning and cultural contestation. One example of modernculture Growing in Bangkalan Madura is Vespa trash culture fan communities. In the communitymany cultural rituals that becomes a lifestyle to be done by community members Vespa fanstrash .Vespa trash culture fan communities grows and develops as a result of the stronglegitimacy of the dominant culture in Bangkalan Madura famous with Islamic culture. Conditionsand cultural situation in Bangkalan be an interesting study to set of problems amid the dominantculture . Spradley as ethnographic data analysis techniques to look for, and gather informationfrom informants who then correlated with the conceptual framework .The results of this thesis describes the form of contestation between the fan communityas a trash Vespa subculture with Islamic religious culture of Madura in the arena of power byrisking their capital in accordance with the realm, featuring a variety of strategies to maintain(Islamic religious Madurese culture) or question the authority of the dominant culture (Vespacommunity). Boarding schools, mosques and religious rituals that culture has led to the momentthe agent out of the structure to-madurese to move to trash vespa fan community anti-structurewith culture of freedom and togetherness or referred to as liminal situation .Keywords : Lifestyle , Power Arena , Liminal Situation.